Regional Economic Development Planning Sustainable (Sytematic Literature Review) - Silvia Arindri Putri; Salahudin Salahudin (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
This study aims to analyze regional economic development planning through land use with a sustainable development model that is studied using the literature review method by reviewing articles in previous research so that it can provide some description and inspiration in providing solutions related to regional economic development planning problems obtained through the site. Scopus and apps with the VOSviewer app. This research will focus on explaining and analyzing thoroughly and specifically related to the implementation of sustainable development, especially in utilizing land in accordance with concepts and ideas that have more ideal development goals and realize sustainable concepts. development Planning. There are several topics that have strong with regional economic development planning, namely, demand, acceptance, urbanization, land use, evaluation, benefits and stakeholders. The limitation of this study is the source of the data obtained because the articles reviewed are only sourced from the Scopus database. Therefore, this study has limited data that can be compared.